The Lost MIS 11c Mammalian Fauna from Via dell’Impero (Rome, Italy) - Maria Rita Palombo; Biagio Giaccio; Lorenzo Monaco; Roberta Martino; Marina Amanatidou; Luca Pandolfi (Quaternary)
This research presents an in-depth analysis of large mammal remains first discovered in 1932 in the archaeological area of ancient Rome, central Italy, during the work for the opening of Via dell’Impero (VFI). This work describes the faunal assemblage, its current preservation status, and uses tephrochronology to assess its age. Additionally, it provides paleoecological insights into the evolution of the mammalian fauna in Latium, central Italy, from MIS 13 to MIS 7. Analysis of the fossils updates the identification previously proposed by De Angelis d’Ossat, confirming the presence of Palaeoloxodon antiquus, Cervus elaphus, and Bos primigenius. However, in contrast to the previous author, the hippopotamus remains are assigned to Hippopotamus cf. antiquus, and a second deer is identified as Dama sp.. Furthermore, gnawing marks on the hippopotamus femur suggest the presence of a middle-sized carnivore. Tephrochronological investigation was conducted on pumice retrieved from the VFI fossiliferous layer and ash extracted from sediments adhering to the fossil surfaces. The major element composition of the glass from all pumice/ash samples shows a strong affinity with the Vico β unit, allowing correlation with the Fucino record and constraining the deposition of the VFI fossiliferous level between <406.5 ± 1.3 ka and >405.7 + 1.5/−1.6 ka. Radiometric dating is particularly useful for large mammal faunas of MIS 11-MIS 7, a period lacking significant faunal renewals, as Latium mammalian faunas are often dominated by species (elephants, red deer, aurochs) with broad chronological ranges.